The significance of failed election in 1993 for Nigeria’s democratic development (2017)
Election plays a vital role in a system of representative democracy. In Nigeria, the history of elections has been a chequered one. From 1964,1979 to 1983 elections in Nigeria, experience shows that the country failed to conduct credible elections which will move the country to a higher rung on the democratization ladder. Thus, successive elections in Nigeria lacked the essential ingredients of democratic electoral processes. However, the June 12 1993 Presidential election remains a watershed in the history of elections in the country. The election was adjudged the most peaceful, and the freest in Nigeria’s post-independence political history. The results of the election were not released by the military government with no justifiable reason. All domestic pressures to make the military allow the winner, M.K.O. Abiola assumed presidential office proved abortive. The 1993 presidential election explains the important roles of individuals, civil society organizations, opposition parties, and foreign countries in terminating authoritarian regime in Nigeria. The paper posits that the June 12 1993 presidential election was very significant for three obvious reasons. First, it allowed Nigeria to slightly conform to the global norm of democracy. Secondly, Nigeria became an encouragement for other countries in Africa in returning to democratic rule. Thirdly, Nigerians were more enlightened to reject any government coming ”to power through military coup. Arising from the foregoing, the paper concludes with some recommendations on how to consolidate democracy in Nigeria